HOW NURSERY RHYMES INTRODUCE WORD FORMATION TO YOUNG CHILDREN: A STUDY ON COCOMELON NURSERY RHYMES SONG LYRICS - Febriola Eklesia; Maria Dewi Rosari (IKIP Siliwangi, 2023)
This research aims to explore the most dominant word-formation process used in the well-known nursery rhymes providers named CoComelon and found out the extent to which they provide exposure of English word-formation to young children. The data source is taken from 40 song lyrics of 4 CoComelon nursery rhymes albums which were transcribed through their official YouTube channel. This study’s main theories were adopted from the word formation processes of O’Grady & Archibald (2019) and the nature of language in L1 and L2 learners of Saville-Troike, M., & Barto, K. (2016). The method used in this research is qualitative method. It begins with selecting words (which formed through the process of word formation) from the transcript lyrics, record it in the predesigned table, then analyzed all. After analyzing, the researchers recorded the related data. The results revealed that out of 9 word formation processes used in CoComelon song lyrics, the inflection process is the dominant one. Through its findings, it is concluded CoComelon facilitate children through it lyrics as the inflection which are said to be mastered first by L1 and L2 English learners, dominantly used in CoComelon song lyrics. Keywords: Word-Formation; Nursery Rhymes; Second Language Acquisition